Latent protective effects of breastfeeding on late childhood overweight and obesity: A nationwide prospective study. (17th March 2014) - Jwa, Seung Chik; Fujiwara, Takeo; Kondo, Naoki
<x xml:space="preserve">Abstract</x> Objective To investigate the latent effect of breastfeeding on overweight and obesity in late childhood. Methods Data on breastfeeding and child anthropometric measurements were collected annually from a nation‐wide population‐based prospective cohort study in Japan (21, 425 boys and 20, 147 girls). Breastfeeding status (exclusiveness and duration) was assessed when the child was 6 months old. Mixed effects models were used to evaluate trajectories of body mass index (BMI), together with overweight and obesity status, from 1.5 to 8 years of age. Results Mixed‐fed boys and exclusively breastfed boys showed lower BMI as the main effect, as well as a slower increase of inclination in BMI as interaction term between feeding type and age, than exclusively formula‐fed boys. Breastfed boys had lower BMI at the ages of 7 and 8, in comparison with exclusively formula fed boys (P = 0.002 and P < 0.001, respectively). A similar association was found for girls, although the main effect of feeding type was not statistically significant. The analysis of breastfeeding duration had similar results. Conclusions Breastfeeding, even if partial or for short duration, has a latent protective effect against overweight and obesity in late childhood, especially for boys.